Cultural Policy in Singapore: Negotiating Economic and Socio-Cultural Agendas - Kong, Lily (Institutional Knowledge at Singapore Management University, 2000)
In this paper, I examine the role of cultural policy in a newly industrialised economy, which is at the same time a state with a short history and only nascent beginnings in nation-building and efforts to construct a distinctive cultural identity. Using Singapore as the site of analyses, develop an understanding of the intersection between the economic and socio-cultural agendas behind cultural development policies. I illustrate the hegemony of the economic, supported by the ideology and language of pragmatism and globalisation. At the same time, I explore the reception of and attempts to negotiate (and at times, contest) state policies by "cultural practitioners" - artists, dancers, playwrights, actors, directors and so forth, illustrating the disjuncture between state policies and practitioners' ideals. This may be cast as a conflict between social and cultural development priorities as envisaged by the practitioners as opposed to economic development priorities as embodied in the state's cultural economic policies.